Life threatening non-accidental burns, pandemic dependent telemedicine, and successful use of cultured Zurich Skin in a neonate - A case report - Clemens Schiestl; Marcello Zamparelli; Martin Meuli; Fabienne Hartmann-Fritsch; Annachiara Cavaliere; Kathrin Neuhaus; Ernst Reichmann; Sophie Böttcher-Haberzeth (Elsevier, 2023)
Life threatening burns of non-accidental origin in neonates are extremely rare. Their management represents a great challenge, particularly since necrosectomy of deep burns and grafting at this young age are technically very demanding. Thus, a strategic surgical master plan is mandatory to achieve rapid and definitive autologous coverage and avoidance of undue risks and iatrogenic burden for the fragile neonatal patient. We present the case of a four day-old neonate who sustained non-accidental deep burns involving 40 % of its total body surface area (TBSA) and the successful application of a laboratory grown, autologous dermo-epidermal skin analogue, termed Zurich Skin (also named denovoSkin), within a clinical trial sub-study. Due to COVID-19 pandemic restrictions, a telemedicine-based approach was installed and a total of 260 cm2 Zurich Skin were transplanted, video assisted, on a wound bed previously prepared with a dermal substitute, thereby covering 20 % TBSA. Take of Zurich Skin was excellent on the chest, good to moderate on the abdomen, and poor on other small areas, where we observed a prolonged healing. After maturation, Zurich Skin showed a close to natural skin coverage without need for further reconstructive surgery. This unique case delivers the proof of concept that Zurich Skin can be successfully applied in early life and even under most adverse medical and paramedical circumstances, provided a carefully crafted masterplan properly addressing the key issues can be executed by joint forces of committed partner institutions.